Immigration, territory and school: a non-equilateral triangle (European Journal of Child Development, Education and Psychopathology, 2019)
In Catalonia, since the end of the 20th century, international immigration has introduced a new element of diversity in the territory, society and school. Social processes of segregation related to immigration are added to the fluctuating balance that these elements maintain within a society and its political project. The school has faced new social and educational demands for which it has had to devise new training responses in line with the new social components. The statistical data of the INE, IDESCAT, the Ministry of Education and the Ministry of Education of the Autonomous Government, show a reality to which immigration adds a component of cultural and religious diversity. This article analyzes the data available until 2018, making a special emphasis on foreign students enrolled in the schools of primary education of Catalonia, taking into account the educational stage, the ownership of the center, the country of origin and the territory. The unequal relationship between immigration, territory and school affects strategies for adapting educational processes and shows the challenges that must be faced.